2013
DOI: 10.1371/journal.pone.0069015
|View full text |Cite
|
Sign up to set email alerts
|

Climate-Induced Changes in Grapevine Yield and Must Sugar Content in Franconia (Germany) between 1805 and 2010

Abstract: When attempting to estimate the impacts of future climate change it is important to reflect on information gathered during the past. Understanding historical trends may also aid in the assessment of likely future agricultural and horticultural changes. The timing of agricultural activities, such as grape harvest dates, is known to be influenced by climate and weather. However, fewer studies have been carried out on grapevine yield and quality. In this paper an analysis is undertaken of long-term data from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
60
2
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 38 publications
3
60
2
1
Order By: Relevance
“…Van Leeuwen et al, 2004;Fraga et al, 2014) and phenological development (Jones & Davis, 2000). Previous research has shown that climatic factors are the main drivers of vineyard yield (Santos et al, 2011;Bock et al, 2013) and wine quality (Jones et al, 2005b;Orduna, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Van Leeuwen et al, 2004;Fraga et al, 2014) and phenological development (Jones & Davis, 2000). Previous research has shown that climatic factors are the main drivers of vineyard yield (Santos et al, 2011;Bock et al, 2013) and wine quality (Jones et al, 2005b;Orduna, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…During the last decades, most of the world's highest quality wine-producing regions have shown a warming trend during the growing season (Duchêne and Schneider, 2005;Jones et al, 2005). This change has led to an advance in phenology, which, jointly with some changes in cultural practices, resulted in earlier harvest dates, higher sugar concentration in grapes, and higher alcoholic concentration in wines (Duchêne and Schneider, 2005;Ramos et al, 2008;Tomasi et al, 2011;Neethling et al, 2012;Webb et al, 2012;Bock et al, 2013;Koufos et al, 2014;van Leeuwen and Darriet, 2016). Higher berry sugar content usually implies higher must pH, which results in less stable, less colored, leaner wines (Ribéreau-Gayon et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…4 An elevated atmospheric CO 2 concentration may result in a greater accumulation of total biomass and, consequently, increased yield. 4,5 Growth period temperature influences phenology and the length of the growing season, and earlier harvest dates are expected with high temperatures. As a consequence of CO 2 and temperature increases, the yield, grape composition and quality will be affected.…”
Section: Introductionmentioning
confidence: 99%